The Effect of Good Governance and Information Technology on the Implementation of Accrual-Based Accounting to Regional Properties - Firmansyah, Amrie; Wibowo, Puji; Wibowo, Puji; Puspitarini, Intan (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to examine the effect of good governance and information technology on the application of accrual accounting to regional property in Indonesia. The change in the accounting system from cash to accruals to full accruals in 2015 resulted in a significant impact on the adoption of accounting for regional assets dominated by fixed assets. The testing method used in this research is to use quantitative methods. This study uses a questionnaire as a tool to collect research data. The population in this study is the manager of district/city government goods in the Province of Bali / Yogyakarta Special Region. Based on the number of questionnaires that have been filled by respondents through Google form, the sample that can be used in this study amounted to 241 respondents.The results of this study conclude that good governance is positively associated with the implementation of accrual-based accounting on regional property. However, information technology is not associated with the implementation of accrual-based accounting on regional property. The results of this study indicate that good governance is an essential factor in strengthening the implementation of accrual-based accounting at the local government level. Furthermore, the information system, which in the management of the financial system including the provision of information on regional property needs to be conducted uniformly, is used by the regional government.